2020
DOI: 10.1002/jcb.29703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional circRNA/miRNA/mRNA regulatory network for exploring prospective therapy strategy of colorectal cancer

Abstract: Circular RNA (circRNA) has been reported to have great scientific significance and clinical value in multiple cancers including colorectal cancer (CRC). However, the biological function of most circRNAs in CRC is still in its infancy. Herein, we discovered the differential expressed circRNAs (DECs) between CRC tissues and matched adjacent using deep RNA sequencing and further confirmed the DECs expression by combining with another Gene Expression Omnibus dataset. Furthermore, we validated the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Additional file 1. Expression profiling of circRNAs in colorectal cancer [212][213][214][215][216][217][218][219][220][221][222][223].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Additional file 1. Expression profiling of circRNAs in colorectal cancer [212][213][214][215][216][217][218][219][220][221][222][223].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For instance, Li et al found that KCNQ1OT1 silencing alleviates high glucose (HG)-mediated proliferation, oxidative stress, and deposition of ECM in mesangial cells through mediating miR-18b/HMGA2 signaling [ 7 ]. Wang et al demonstrated that lncRNA CTBP1-AS2 attenuates HG-mediated oxidative stress, the deposition of ECM, and inflammatory response in mesangial cells by sponging miR-155-5p to induce FOXO1 expression [ 8 ]. lncRNA cancer susceptibility candidate 2 (CASC2) is reported to suppress DN progression through different signaling axes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…multiple circRNAs have been proven to be vital mediators in the development of IBD and colon cancer (Zheng et al, 2019;Lin et al, 2020a), compounds such as rutin and ergometrine have been identified to regulate lncRNA/circRNA/miRNA/mRNA networks to inhibit colon cancer, implying that RNA-based networks can also be used as effective treatments in the future (Lin et al, 2020b;Xu et al, 2020).…”
Section: Downloaded Frommentioning
confidence: 99%